Unveiling Language Prejudice: A Corpus-Based Analysis of Racial Slurs Across Genres - Rahman, Fadhlur; Yuzar, Ella; Kholid, Mohammad (JOLLT Journal of Languages and Language Teaching, 2024)
Discrimination and racism have been obvious for decades. This encompasses derogatory racial epithets such as "nigger, niggers, n-words". The objective of this study was to employ corpus-based analysis in order to examine the frequency of racial derogatory expressions across various genres of literature. The COCA (Corpus of Contemporary American English) data were employed to perform a corpus-based linguistic analysis of the terms 'nigger', 'niggers', and 'n-word' over a span of 20 years (1990 to 2019).Â  Although the words "niggers" and "n-word" have similar meanings, the occurrence of the word "niggers" and "n-word" in the corpora was significantly less frequent compared to the word "nigger." Primarily, the term "niggers" was used as a plural indicator for the derogatory term "nigger". The frequency with which individuals who use derogatory language, such as the term "niggers," associate themselves with pronouns like "they," "us," "those," "all of you," etc., suggests the existence of these patterns. The sole term that displays a notably diverse frequency distribution across genres is the n-word (in comparison to these two terms).